2015
DOI: 10.17135/jdhs.2015.15.6.825
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Depression, Stress, and Self-Esteem with Oral Health-Related Quality of Life of Middle-Aged Women

Abstract: The purpose of this study was to examine the relationships between depression, stress, self-esteem, oral health-related quality of life in middle-aged women. Data were as collected by self-reported questionnaires from 205 middle-age women. The instruments were the Center for Epidemiologic Studies Depression scale (CES-D), Brief Encounter Psychosocial Instrument (BEPSI), Self-Esteem Scale (SES). The data were analyzed using t-test, one-way ANOVA, Pearson correlation coefficients and multiple regression with IB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Our results are consistent with those of previous studies, namely, that depression was associated with a worsening of overall oral health-related quality of life. For example, one study found that the oral health impact profile was significantly associated with depression, stress, and self-esteem in community-dwelling middle-aged women ( 21 ). Although this was a cross-sectional study, the Pearson correlation coefficient of the correlation with depression ( r = −0.560, p < 0.001) revealed a highly statistically significant outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with those of previous studies, namely, that depression was associated with a worsening of overall oral health-related quality of life. For example, one study found that the oral health impact profile was significantly associated with depression, stress, and self-esteem in community-dwelling middle-aged women ( 21 ). Although this was a cross-sectional study, the Pearson correlation coefficient of the correlation with depression ( r = −0.560, p < 0.001) revealed a highly statistically significant outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies that showed that halitosis lowers self-esteem [7], it was determined that self-esteem could be improved if halitosis is reduced through oral-probiotic intake. In addition, in a study that reported that good oral-health-related quality of life increases selfesteem [31], it was inferred that if halitosis is reduced after the ingestion of oral probiotics, and oral-health-related quality of life is improved, then self-esteem can be increased. However, in this study, there was no statistically significant differences in self-esteem after ingestion of the oral probiotic.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of older people is rapidly increasing, due to ageing around the world . An ageing society and concurrent increases in living standards have been accompanied by an increasing desire to maintain good health and high quality of life in older age . In middle age, oral health has a substantial impact on an individual’s overall health, and masticatory ability plays a particularly important role because of its ability to influence nutritional intake .…”
Section: Introductionmentioning
confidence: 99%